miR-193b and miR-30c-1* inhibit, whereas miR-576-5p enhances melanoma cell invasion in vitro - Kordaß, Theresa; Weber, Claudia; Eisel, David; Osen, Wolfram; Eichmüller, Stefan B. (OncoTarget, 2018)
In cancer cells, microRNAs (miRNAs) are often aberrantly expressed resulting in impaired mRNA translation. In this study we show that miR-193b and miR-30c-1* inhibit, whereas miR-576-5p accelerates invasion of various human melanoma cell lines.
Gesehen am 21.01.2020